The price index - Afriat, S. N. (Cambridge, [Eng.] : Cambridge University Press, 1977)
This is the monthly consumer price index (CPI) in Yukon for February 2009. Includes the consumer price index, consumer price index history (annual averages), and the annual average rate of inflation in Whitehorse compared to Canada.
Includes bibliographical references: p. [171]-187.
aia 03/05/2018
Loans
Keywords: Price indexes; Prices Indices